USM TARGETS 5,000 INTERNATIONAL STUDENTS BY 2020 - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 30 March 2015 Universiti Sains Malaysia (USM) aims to increase its international students intake to 5,000 by 2020, in line with the University’s internationalisation efforts. The target is among those detailed on the USM internationalisation policy for the next five years, along with other selected programmes to be implemented intensively involving the university community.